Introducing Maya 2009 - Derakhshani, Dariush (Wiley Pub., 2009)
"If you're new to Maya, the industry-leading 3D animation and effects software, Introducing Maya includes step-by-step tutorials and easy-to-follow explanations to teach you the basics and nuances of this complex software. Whether you're a student or a hobbyist, you can learn all about the Maya interface and the fundamentals of modeling, texturing, animating and visual effects with realistic examples. If you're new to 3D animation or transitioning from another 3D application, this book will provide you with the tools you need to become proficient at Maya"--Resource description page